2018
DOI: 10.1111/1365-2664.13094
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐based selection of nurse plants to restore ecosystem functions in mine tailings

Abstract: Metal mining in drylands generates waste tailings with high toxicity, physical instability, as well as water and thermal stresses that hamper their biological colonization. This limits the restoration of ecosystem functions that are essential to re‐integrate these artificial micro‐deserts within the landscape matrix. We assessed the functional role of local nurse plant species and their traits to restore ecosystem functions related to soil fertility, soil microbial productivity and the reduction of abiotic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 44 publications
1
57
0
1
Order By: Relevance
“…Indeed, we have previously shown that some of the five nurse species used in this experiment have morphological and physiological traits that not only facilitate the establishment of other plants, but also induce a faster recovery of soil fertility, rates of organic matter decomposition and nutrient cycling or resistance to erosion (Navarro-Cano et al, 2018). This opens up the possibility to restore not only species populations and ecological interactions, but also relevant ecosystem functions (Navarro-Cano, Goberna, Valiente-Banuet, & Verdú, 2016).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Indeed, we have previously shown that some of the five nurse species used in this experiment have morphological and physiological traits that not only facilitate the establishment of other plants, but also induce a faster recovery of soil fertility, rates of organic matter decomposition and nutrient cycling or resistance to erosion (Navarro-Cano et al, 2018). This opens up the possibility to restore not only species populations and ecological interactions, but also relevant ecosystem functions (Navarro-Cano, Goberna, Valiente-Banuet, & Verdú, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…Functionally diverse neighbourhoods provide elevated rates of ecosystem processes related to primary productivity, soil fertility, nutrient cycling, resistance to invasion or recruitment of new plant species (Dı́az & Cabido ; Funk, Cleland, Suding, & Zavaleta, ; HilleRisLambers, Adler, Harpole, Levine, & Mayfield, ). Indeed, we have previously shown that some of the five nurse species used in this experiment have morphological and physiological traits that not only facilitate the establishment of other plants, but also induce a faster recovery of soil fertility, rates of organic matter decomposition and nutrient cycling or resistance to erosion (Navarro‐Cano et al, ). This opens up the possibility to restore not only species populations and ecological interactions, but also relevant ecosystem functions (Navarro‐Cano, Goberna, Valiente‐Banuet, & Verdú, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While trait‐based restoration approaches are often used to select species for restoration, primarily focusing on traits associated with resource use, competition, and effects on ecosystem processes (Funk et al ; Kimball et al ; Ostertag et al ), selecting anti‐herbivory traits (unpalatable secondary compounds, protective structures, etc.) may have a greater impact on increasing the success of native establishment in CSS (Reader ; Gómez‐Aparicio et al ; Navarro‐Cano et al ). Planting unpalatable species around palatable ones may also deter herbivory of target species that are being restored (Callaway et al ; Smit et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In coastal sage scrub, non-native grasses also experience herbivory, and herbivores may help to reduce the competitive effects of nonnatives (DeSimone & Zedler, 2001;Wainwright, Wolkovich, & Cleland, 2012). In Mediterranean-climate systems, adult shrubs may act as "nurse plants" by creating moist microsites that increase germination and early growth of native shrub seedlings (Cuevas, Silva, Leon-Lobos, & Ginocchio, 2013;Navarro-Cano, Verdu, & Goberna, 2018;Padilla & Pugnaire, 2006). Alternatively, adult shrubs may compete with seedlings for limited water, decreasing seedling survival (Marquez & Allen, 1996;Noumi, Chaieb, Michalet, & Touzard, 2015).…”
mentioning
confidence: 99%